ACTIVIDAD ANTIMICROBIANA IN VITRO DE UN PROPÓLEO DE SANTANDER SOBRE ENTEROCOCCUS FAECALIS (2012)
Objective: to evaluate the antimicrobial activity of an ethanolic propolis extract from Santander province against Enterococcus faecalis.Methods: an experimental In vitro study was made. Starting from pristine propolis collected in the city of Lebrija (Santander), an ethanolic extract was obtained using a Soxhlet apparatus. The antimicrobial activity was measured using the macro dilution tube technique by counting the Colony Forming Units (CFU) per mL after 48 hours. Propolis solutions with concentrations in the range from 100 to 0.19 mg/mL were evaluated. Tubes containing dilutions of the antibiotic norfloxacin and solvent (96% ethanol) were used as reference and control.Results: the propolis solutions within the range from 100 mg/mL to 50 mg/mL inhibited 100% growing of E. faecalis. Propolis extract showed an inhibitory concentration 50 (IC50) of 1.19 mg/mL and an inhibitory concentration 90 (IC90) of 7.92 mg/mL respectively. Norfloxacin on the other hand was more effective with IC50 and IC90 of 0.06 and 2.39 µg/mL respectively. Ethanol showed non-antimicrobial activity at the concentration present within the extracts.Conclusion: with further studies support it would be possible to suggest the use of propolis from Santander as an alternative of irrigation and medication in endodontics because of its powerful effect against E. faecalis considering it is the most frequent pathogen found in persistent infections.